Тренди ливарної промисловості в країнах, що є сусідами з Україною - Гнатуш, В. А.; Дорошенко, В. С. (Physico-technological Institute of Metals and Alloys, 2023)
The review of the current state of the foundry industry of countries, territorial neighbors of Ukraine, reflects the level of production and technical potential, as well as the degree of utilization of foundries of the countries, which are the most likely competitors of our country in this industry. Such a comparative review can serve as the basis for planning measures for the restoration and innovative development of the foundry industry of Ukraine. The technical and economic processes of neighboring countries have a number of similar properties and interconnections, which affects their production volumes, the state of scientific and technological resources, the process of development of the region's industry, and vital signs of the population. The foundry industry of each of the countries, territorial neighbors of Ukraine, has its own, historically established features. At the same time, Poland, Hungary and Romania, as well as Turkey, are quite consistently and actively modernizing their foundry industry, taking advantage of the advantages of the European Community. The most detailed technological processes and the structure of the production of castings by metals of countries such as Russia and Belarus, previously particularly closely cooperating and collaborating in foundry production with Ukraine, are examined. The leadership of Belarus and Russia after defragmenting the Union did not pay due attention to both foundry and engineering as a whole. However, in 2016 in Belarus, the modernization and implementation of innovative technologies in foundry was stimulated by an order of the Ministry of Industry. Recently, optimistic forecasts have also appeared in Russia. The 4th Industrial Revolution, which began at the beginning of the XXI-th century, is a challenge for the economies of Russia, Belarus and Ukraine. Without these countries actively modernizing their foundry industry, its production and technological level risks even lagging behind the global one.